Radiotherapy treatment of the common Keira's erythroplasia form - F. R. Dzhabarov; A. B. Alnikin; V. G. Tolmachev (Вестник урологии, 2021)
Bowen's disease, Keira's erythroplasia and bowenoid papulosis are currently classified as precancerous penis lesions associated with human papillomavirus (HPV). The diagnosis and treatment of precancerous penis lesions is a unique challenge. Most of our knowledge about these diseases is based on small, non-randomized retrospective studies due to the rarity of these conditions and the low incidence of penile cancer.The article provides an overview of the most significant papers on the topic of precancerous penis lesions. In addition, a case of successful Keira's erythroplasia recurrence treatment using close-focused radiotherapy is also described.